Síndrome de Burnout: estudo com profissionais de Enfermagem que atuam em Centro de Terapia Intensiva - Santiago, Tainá de Araújo (2018)
Introduction: Burnout Syndrome or Occupational Exhaustion Syndrome affects individuals from occupations that deal with people, causing emotional exhaustion or exhaustion, referring to feelings of fatigue and difficulty in dealing with stressful situations. This dissertation was formed by two articles. The first, theoretical, is entitled "Burnout Syndrome in Nurses of Intensive Care Units: a bibliometric study”. Objective: To characterize the scientific production about Burnout Syndrome in nurses who work in Intensive Care Units. Methodology: This is a bibliometric study, with a quantitative and documentary approach, based on the online search in the databases of the Virtual Health Library (VHL) and the Capes Portal, in articles published between 2000 and 2017 in Portuguese, English and Spanish, with complete texts, making a total of 46 articles. Results: A greater number of publications were observed as of 2011. With regard to journals, 30 were responsible for disseminating studies on the subject. As for language, Portuguese predominated. The descriptors Burnout Syndrome, Intensive Care Unit and Nursing were the ones that had the highest incidence. The words that represented the highest semantic content in the studied subject and that were most distinguished by the high frequency in the texts analyzed were burnout, professional, nurse, hospital and therapy. Conclusion: It was possible to observe that studies in this area are progressing more and more. However, there is still an incipient scientific production on the subject. Introduction: The second article deals with an original research, entitled: "Prevalence of Burnout Syndrome in the Nursing team of an Intensive Care Center", whose objective was: to identify the prevalence of Burnout Syndrome and its relationship with some sociodemographic, in the Nursing team, which works in an Intensive Care Center of a university hospital, in the municipality of João Pessoa - Paraiba. Methodology: It is a field research, of the exploratory type, with quantitative approach. The study population involved the Nursing team, composed of nurses and technicians, who work in the Intensive Care Units. The data were collected through a structured questionnaire and a validated instrument; were coded and analyzed statistically. Results: The study was attended by 115 nursing professionals, predominantly female, married, with children and aged between 25 and 59 years. Most nurses have a median level for Burnout Syndrome. However, among the factors associated with the syndrome, it was verified that some of the studied variables show a greater vulnerability: they are: gender, marital status, remuneration and time of professional performance. Conclusion: The verified data are worrisome, considering the perception of the great prevalence of Burnout Syndrome among the professionals that composed the present study, demonstrating that there is a great exposure of this team to factors determining to the sickness.